The Urgency of Enacting Legislation on Asset Forfeiture from Corruption Crimes - Hutajulu, Johanes Alfredo; Hufron, Hufron (SEED: Journal of Scientific Research, 2025)
Technological developments and globalization also contribute to the complexity of corruption crimes. Information and communication technology allows corrupt actors to hide their traces more sophisticatedly, making it difficult to investigate and enforce the law. As a concrete step in supporting the confiscation of assets resulting from criminal acts, there is a discourse to specifically regulate the confiscation of assets through a separate law. As a concrete step in supporting the confiscation of assets resulting from criminal acts, there is a discourse to specifically regulate the confiscation of assets through a separate law. This study aims to find out how urgent it is to establish a law on the confiscation of assets resulting from corruption crimes. This study use a normative juridical research method using a conceptual approach and a statutory approach. The results of this study show that the establishment of a law on the confiscation of assets resulting from corruption crimes is an indispensable step in Indonesia considering the complexity and wide impact of corruption crimes. Corruption not only harms the country's finances but also reduces public trust and hinders economic development. The implementation of the asset forfeiture law cannot run effectively without the active role of supervisory and law enforcement agencies such as the Corruption Eradication Commission (CEC), the Financial Transaction Reporting and Analysis Center (FTRAC), and the Prosecutor's Office. These institutions play a role in tracking, supervising, and implementing the confiscation of assets derived from corruption crimes.